Intelligent manufacturing system based on data mining algorithm. (2nd December 2021) - Liu, Xiaoya; Zhou, Qiongjie
This article focuses on the evaluation model of intelligent manufacturing system based on data mining algorithm. Combining data mining algorithm with intelligent manufacturing system, the evaluation model of intelligent manufacturing system is established successfully. According to the characteristics of intelligent manufacturing system, the data is divided into training set, cross-validation set and test set, and then the training set is used to perform neural network training, adjustment and optimisation and verification set. The experiment found that the accuracy rate of the training group was higher than that of the test group, the highest accuracy rate of the training group was 69%, and the highest accuracy rate of the test group was 32.5%. The results show that using data mining algorithms for recognition can effectively cluster control chart patterns and improve recognition efficiency.